Transformasi Pembelajaran Melalui Digital Twin: Systematic Literature Review Lintas Jenjang Pendidikan - Diana Qisthin Thoniyah; Suprih Widodo; Ulva Elviani (Universitas Multi Data Palembang, 2025)
Digital Twin (DT) is an innovative technology that creates virtual replicas of physical entities to simulate real-world behavior through real-time data. Although it has been successfully implemented in manufacturing, healthcare, and agriculture sectors, the application of DT in education remains fragmented and focused on specific domains. This study aims to conduct a systematic literature review to identify DT applications in education across various levels, map implementation methodologies, analyze impacts on learning outcomes, and identify challenges and best practices. The method used is a systematic literature review with the PRISMA framework. The search was conducted on the Scopus database for the period 2020-2025 using keywords related to Digital Twin, assessment, and education, yielding 773 articles which were then filtered to 32 final articles. After undergoing quality assessment, 17 articles were selected for further analysis. The research findings indicate that DT enhances students' conceptual understanding and practical skills, supports simulation-based learning, personalized learning, and remote collaboration. These findings provide comprehensive insights into DT utilization that can serve as a reference for researchers, educational practitioners, and policymakers in optimizing the implementation of this technology to improve educational quality.